Temperature Dependence Study of Water Dynamics in Fluorohectorite Clays Using Molecular Dynamics Simulations - H. O. Mohammed; K. N. Nigussa (Advances in Condensed Matter Physics)
We have carried out molecular dynamics (MD) simulation techniques to study the diffusion coefficient of interlayer molecules at different temperature. We have focused on the translation dynamics of water in bihydrated states within the context of water dynamics in clays. We concentrated on temperatures between 293 and 350 K, i.e., the range important to daily life wastewater handling. A natural clay has been modified as a synthetic clay called fluorohectorite clay, and the properties are studied using MD simulations, the result of which allows us to understand the determining parameters through a comparison with experiment values. The activation energy Ea is determined by our simulation to be between [0.09−0.17] eV per particle. The calculated diffusion constants are in the order of 10−5 cm2s−1. The simulation results are in a good agreement with experiments for the relevant set of conditions, and give insight into the origin of the observed dynamics.